Duckling - Shamsie, Kamila, 1973- (Fairy tale revolution., 2021)
A duck unlike other ducks, a raincloud-duck, with the heart of a lion, strikes out into the world on her own. On the farm, some eggs are hatching. A flock of sweet ducklings are popping out but one duckling looks different from all the others. Kamila Shamsie retells The Ugly Duckling with great empathy and a warm heart. Cast out and all alone, the odd duckling will need all her bravery and curiosity to survive. Her journey is a search for belonging, but what she finds is the right to be different.